A influencia da caseína nas alterações hepáticas e cardíacas em ratos submetidos a uma dieta de cafeteria - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Intake of dairy products has been associated with benefits in parameters related to obesity and metabolic syndrome. Casein and its enzymatic hydrolysates have several desirable functional properties and, therefore, there is great interest in their use on a larger scale in the food industry. The present work tested the effect of casein supplementation on anthropometric characteristics: abdominal circumference, final body weight, evolution of body weight, Lee's index, food consumption, perigonadal, mesenteric and retroperitoneal fat, adiposity index, metabolic parameters and histopathological changes in liver and heart of rats. In total, 96 Wistar rats (Rattus norvergicus) were used, 48 females and 48 males 30 days old, where the sexes were divided into two experimental groups. The Cafeteria diet females (FDC) and control females (FC) group and the cafeteria diet males (MDC) and control males (MC) group, and each of these groups were divided into casein supplemented (FDCC; MDCC; FCC; MCC) and not supplemented (FDC; FC; MDC; MC). The cafeteria diet was offered ad libitum daily to the DC group (cafeteria diet) from the 30th day of life. At 60 days of life, the groups MDCC, MCC, FDCC, FCC started supplementation for 30 days with casein using the gavage method. Evaluating the abdominal circumference, the final body weight, the evolution of the body weight and the Lee index, a significant difference was observed in the FDC group when compared to the CF group. A lower weight gain in body evolution is observed only in the FCC group compared to the FC group, with a significant difference of p <0.05. The means of fat in males repeated a pattern of females and also showed a significant difference when purchasing the cafeteria diet and control groups. When comparing the MDC group with the MDCC group, the retroperitoneal fat of the MDCC group decreased, showing a significant difference, and in females, the mesenteric fat showed a significant difference, decreasing when compared the FDCC group with the FDC group. The adiposity index was lower in the FDCC group compared to the FDC group, with p <0.05. And when analyzing the effect of the cafeteria diet we can see that the diet groups had a significantly higher average than the control groups. Energy intake was significantly higher in both females and males who received a cafeteria diet (Females: 187.6 kcal / animal / day; Males: 195.4 Kcal / animal / day) compared to the control group (Females: 112, 2 kcal / animal / day; Males: 160.4 Kcal / animal / day), with p <0.05. In the intraperitoneal insulin resistance test when analyzing the area under the curve, the rats in the cafeteria diet group showed significantly greater insulin resistance than the control rats. The cafeteria diet group showed the highest blood glucose at the point after the administration of the glucose load (30 minutes) with an average of 176.9 ± 68.7mg, when the glucose tolerance test was performed. In the other points, there was no statistically significant difference. When looking at the area under the curve, the effect of casein was significant in the FDCC group, when compared to the FDC group. When analyzing the biochemical parameters, the triglyceride levels of the FDC group were significantly higher compared to the FC group. HDL-c levels were statistically higher for CF compared to the FCC group. The groups supplemented with casein showed a reduction in most liver enzymes, presenting a significance of p = 0.01 for the TGP enzyme when compared to the control group of females (FC) with the supplemented control group (FCC). heart were significantly higher in the FDC than in the CF and in males only the heart weight was significantly higher in the MDC group when compared to the MC. There were no histological changes in the organs. Casein appears to be promising in animals under physiological conditions, since it exerted a statistically significant effect on weight gain, adiposity index and amount of adipose tissue, the TGP enzyme and in the glucose tolerance test. Therefore, additional studies should be carried out over a longer period to verify its possible action in increasing satiety, controlling body mass and metabolic rates and, thus, can serve as an important nutritional resource for the treatment and prevention of metabolic diseases.
Keywords: Caseína. . Índice de adiposidade. Proteínas. Dieta de cafeteria.; Obesidade; Índice de adiposidade; Proteínas. Dieta de cafeteria.; Dieta de cafeteria; Casein; Obesity; Adiposity index; Protein; Cafeteria diet; CNPQ::CIENCIAS DA SAUDE